Direct C−H Arylation of Indole‐3‐Acetic Acid Derivatives Enabled by an Autonomous Self‐Optimizing Flow Reactor. Issue 3 (25th November 2020) - Vasudevan, N.; Wimmer, Eric; Barré, Elvina; Cortés‐Borda, Daniel; Rodriguez‐Zubiri, Mireia; Felpin, François‐Xavier
Abstract: Described herein is a continuous‐flow strategy for the palladium‐catalyzed direct C−H arylation of indole‐3‐acetic acid derivatives with arenediazonium salts. A fully autonomous self‐optimizing flow platform was used to efficiently optimize the coupling reaction in a three‐dimensional space. The flow methodology developed is experimentally simple, mild, broad in scope, and safer than traditional batch approaches. Our continuous‐flow approach is particularly convenient to prepare precursors of pharmaceutically relevant compounds. Abstract :